Perlindungan Hukum Atas Hak Mendapatkan Royalti terhadap Hak Cipta Karya Lagu di Kota Makassar - Asmah; Ichserwanta Syahadat; Muh. Ridwan; Gazali (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2023)
This study aims to analyze the role of legal protection of copyright in supporting the economy of songwriters in Makassar City, while evaluating the contribution of the Yayasan Karya Cipta Indonesia (YKCI) in optimizing the utilization of the economic rights of songwriters in the region. The research locations include Jakarta and Makassar, with a focus on the Head Office of the Directorate General of Intellectual Property Rights, the Office of the Ministry of Law and Human Rights of South Sulawesi, and the Office of the Yayasan Karya Cipta Indonesia. Data collection methods include interviews, observations, and questionnaires. The results of the study indicate that: 1) The government has not provided direct protection for songwriters regarding the receipt of royalties. Current protection is still limited to the implementation of laws and educational efforts to prevent violations. Songwriters need to play an active role in protecting their own rights or hand over the management of these rights to a Collective Management Institution such as YKCI, which is tasked with managing and collecting royalties from users. 2) YKCI has an important role in managing songwriter royalties in Makassar, namely as a collective management institution that collects and distributes royalties to creators. In addition, YKCI also plays a role in taking legal action, both criminal and civil, and demanding compensation if there is a violation of copyright on the songs they manage.